The reciprocal relations among basic psychological need satisfaction at school, positivity and academic achievement in Chinese early adolescents. (February 2021) - Zhou, Jianhua; Huebner, E. Scott; Tian, Lili
Abstract: This study examined the reciprocal relations among basic psychological need satisfaction at school (BPNSS), positivity, and academic achievement in Chinese early adolescents, using a six-wave longitudinal design. A total of 712 students from Grades 7 in China ( M age = 12.92 years, 375 girls) completed measures of BPNSS and positivity in the middle of three consecutive semesters. Students exam scores for Chinese, mathematics, and English courses were obtained from school records at the end of each semester. Structural equation modeling indicated that: (a) BPNSS directly predicted academic achievement and vice versa; (b) positivity directly predicted academic achievement but not vice versa; (c) BPNSS directly predicted positivity and vice versa; (d) BPNSS indirectly predicted academic achievement via positivity; and (e) academic achievement indirectly predicted positivity via BNPSS. The findings are helpful for understanding how BPNSS and positivity temporally interrelate with academic outcomes from a positive youth development perspective. Highlights: Basic psychological need satisfaction at school predicted subsequent academic achievement and vice versa. Positivity predicted subsequent academic achievement but not vice versa. Basic psychological need satisfaction at school predicted subsequent positivity and vice versa. The relation between basic psychological need satisfaction at school and academic achievement was mediated by positivity. Basic psychological need satisfaction at school help to explain the relation between academic achievement and positivity.